2014
DOI: 10.1507/endocrj.ej14-0061
|View full text |Cite
|
Sign up to set email alerts
|

Phantom experiment and clinical utility of quantitative shear wave elastography for differentiating thyroid nodules

Abstract: Recently ultRasonogRaphy equipment has remarkably improved. High-resolution ultrasonography excels in the detection of thyroid lesions, and it is an essential tool for diagnosing thyroid diseases. The present of specific features on B-mode sonography, evaluation of blood flow with Doppler sonography, and the strain ratio measured by strain elastography (SE) provide predictions of tissue characteristics to a certain degree. However, ultrasonography remains suboptimal for diagnosing thyroid diseases [1,2].The no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 16 publications
(18 reference statements)
3
25
0
Order By: Relevance
“…Thus, small nodules are not accurately measured using ARFI because the ROI will contain not only the nodule, but also the surrounding thyroid tissue and the values of velocity measured for that nodule will not be real. On the other hand, Fukuhara et al showed that the measurements of the velocity in nodules smaller than 20 mm in diameter are not stable [92].…”
Section: Limitations and Causes Of False Resultsmentioning
confidence: 99%
“…Thus, small nodules are not accurately measured using ARFI because the ROI will contain not only the nodule, but also the surrounding thyroid tissue and the values of velocity measured for that nodule will not be real. On the other hand, Fukuhara et al showed that the measurements of the velocity in nodules smaller than 20 mm in diameter are not stable [92].…”
Section: Limitations and Causes Of False Resultsmentioning
confidence: 99%
“…Fukuhara et al acknowledge in their study that when objects exhibit small diameters, measurements of SWV parameters are unstable. They interpret the phenomena of this depreciation as being accounted for by the US waves of the push pulse, which were reflected and refracted at the boundaries of the objects, thus resulting in the irregular production of shear waves [15,34]. Such factors in the border area of the phantom object may be responsible for the high relative error of US shear wave elastography measurements when adapting the ROI directly to the shape of the object ("best fitted").…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the measurement procedure in the second part of the study was repeated five times for each target type, with the stiffness value defined as the mean of the five measurements for each ROI diameter (diameters: 40, 38, 36, 34,32,30,28,26,24,22,20,18,16,14,12,10,8,6, 4 and 2 mm).…”
Section: Study Design -Measurement Proceduresmentioning
confidence: 99%
“…Finally, there were 16 studies meeting inclusion criteria in our meta-analysis [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Table 1 presents the main characteristics of the studies.…”
Section: Description and Quality Of Studiesmentioning
confidence: 99%